Acute silicosis in a patient with Tuberculous Lymphadenitis - Samad, Abdul; Butt, Nauman Ismat; Naz, Farah; Zahid, Ayesha; Ghoauri, Muhammad Sohail Ajmal; Ashraf, Tehzeeb (International Journal of Pathology, 2025)
Background: Excessive exposure to airborne crystalline Silica can result in irreversible lung inflammation, and fibrosis.Case Report: A 22-year man presented with shortness of breath and persistent cough for 3 days. He was taking oral anti-tuberculous therapy for tuberculous lymphadenitis diagnosed by cervical lymph node biopsy for the last 9 months. He had right sided spontaneous pneumothorax 3 months ago, chest tube thoracostomy and pleurodesis with doxycycline were done. For the last 1 year, he had been working in a cement factory but previously was employed in rice shelling. His chest X-ray demonstrated a right sided pneumothorax, non-homogenous opacifications in middle and lower zones bilaterally. HRCT chest revealed bilateral ground-glass opacifications with nodularities and infiltrates more pronounced peripherally. He was diagnosed as having Acute Silicosis based on radiographic findings and occupational history. He was managed with oxygen inhalation therapy and intravenous steroids.Conclusion: Counseling regarding occupational rehabilitation was done.